Executive Function Is Related to the Urinary Urgency in Non-demented Patients With Parkinson’s Disease - Tkaczynska, Zuzanna; Becker, Sara; Maetzler, Walter; Timmers, Maarten; Van Nueten, Luc; Sulzer, Patricia; Salvadore, Giacomo; Schäffer, Eva; Brockmann, Kathrin; Streffer, Johannes; Berg, Daniela; Liepelt-Scarfone, Inga (Frontiers in Aging Neuroscience, 2020)
INTRODUCTION: Evidence suggests urinary urgency is associated with cognitive impairment in a subtype of Parkinson’s disease (PD) patients. This study investigates if cognitive impairment independently predicts the presence of urinary dysfunction. METHODS: We report data of 189 idiopathic PD patients, excluding those with concomitant diseases or medication interacting with bladder function. A standardized questionnaire was used to define presence of urinary urgency. All patients underwent a comprehensive motor, cognitive non-motor and health-related quality of life (HRQoL) assessment. Multivariable linear regression analysis was performed to identify independent variables characterizing urinary urgency in PD (PD-UU), which were assigned as discriminant features to estimate their individual contribution to the phenotype of PD-UU group. RESULTS: Of 189 PD patients, 115 (60.8%) reported PD-UU. The linear regression showed that among cognitive domains, executive function (EF) (p = .04) had a significant negative association with PD-UU. In a second model, scores of the Montreal Cognitive Assessment (MoCA) significantly differentiated between study groups (p = .007) and with non-motor symptom (NMS) burden (p < .001). The third model consisted of reports of HRQoL, of which stigma was the only subscale of the Parkinson’s Disease Questionnaire (PDQ-39) differentiating between patients with and without PD-UU (p = .02). Linear discriminant analysis provided evidence that the combination of EF, NMS impairment, nocturia and stigma discriminated between groups with 72.4% accuracy. CONCLUSION: In our large, non-demented PD cohort, urinary urgency was associated with executive dysfunction, supporting a possible causative link between both symptoms. A combination of neuropsychological and non-motor aspects identified patients with PD-UU with high discriminative accuracy.